1999
DOI: 10.2135/cropsci1999.3961728x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mapping of Loci for Agronomic Traits on Chromosome 3A of Bread Wheat

Abstract: Advanced wheat lines carrying the Hessian fly resistance gene H27 were obtained by backcrossing the wheat/Aegilops ventricosa introgression line, H-93-33, to commercial wheat cultivars as recurrent parents. The Acph-N v 1 marker linked to the gene H27 on the 4N v chromosome of this line was used for marker assisted selection. Advanced lines were evaluated for Hessian fly resistance in field and growth chamber tests, and for other agronomic traits during several crop seasons at different localities of Spain. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
91
0
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(104 citation statements)
references
References 24 publications
11
91
0
2
Order By: Relevance
“…Moreover, chromosome-specific recombinant inbred lines (RILs) or recombinant substituted (RS) lines can be used to separate, identify, and map gene(s) controlling agronomic traits and fiber traits by linkage with molecular markers (Kaeppler 1997;Shah et al 1999). Studies have demonstrated the advantages of QTL mapping using chromosome substitution and chromosome-specific recombinant lines in wheat, tomato, and mice (Zemetra et al 1986;Zemetra and Morris 1988;Yen and Baenziger 1992;Weide et al 1993;Shah et al 1999;Nadeau et al 2000;McDonald et al 2001). Indeed, we are developing RS populations to be used for high-resolution dissection and mapping of the QTL governing cotton yield and fiber qualities.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, chromosome-specific recombinant inbred lines (RILs) or recombinant substituted (RS) lines can be used to separate, identify, and map gene(s) controlling agronomic traits and fiber traits by linkage with molecular markers (Kaeppler 1997;Shah et al 1999). Studies have demonstrated the advantages of QTL mapping using chromosome substitution and chromosome-specific recombinant lines in wheat, tomato, and mice (Zemetra et al 1986;Zemetra and Morris 1988;Yen and Baenziger 1992;Weide et al 1993;Shah et al 1999;Nadeau et al 2000;McDonald et al 2001). Indeed, we are developing RS populations to be used for high-resolution dissection and mapping of the QTL governing cotton yield and fiber qualities.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned previously, Pugsley (1983) and White and Hoogenboom (2003) have suggested that wheat phenology could be largely explained by genes controlling plant height (Rht), photoperiod (Ppd), and vernalization (Vrn). Certainly progress has been made in mapping (Laurie, 1997;Shah et al, 1999;Kato et al, 1999;Sourdille et al, 2000;Iwaki et al, 2002;Toth et al, 2003) and cloning (Danyluk et al, 2003;Peng et al, 1999;Trevaskis et al, 2003;Yan et al, , 2004 these genes. In addition, some of the necessary information on the physiological aspects of these genes may be obtained from other genera.…”
Section: Plant Height Genesmentioning
confidence: 99%
“…It was suggested in the same study that these genes fine-tune flowering time probably by determining the amount and rate at which vegetative and floral primordia are produced. A detailed mapping in bread wheat has detected eps loci on chromosomes of homologous group 2 and on the short arm of chromosome 3A [65,66]. A locus on chromosome 2B is orthologous with the eps2 gene in barley (Hordeum vulgare) [6,11,64], whereas the one on chromosome 3A is orthologous with the Eps-3Am gene in einkorn wheat (Triticum monococcum) [67].…”
Section: The Influence Of Earliness Per Se (Eps) Genes On the Flowerimentioning
confidence: 99%
“…A locus on chromosome 2B is orthologous with the eps2 gene in barley (Hordeum vulgare) [6,11,64], whereas the one on chromosome 3A is orthologous with the Eps-3Am gene in einkorn wheat (Triticum monococcum) [67]. The locus on chromosome 3A has been reported to also have significant effects on plant height, thousand kernel weight, and number of grains per plant [66]. However, no eps genes have been cloned as yet in bread wheat [12,68] as compared to barley [6,61,69] and einkorn wheat [67].…”
Section: The Influence Of Earliness Per Se (Eps) Genes On the Flowerimentioning
confidence: 99%